Chapter Predoni a casa nostra e il geografo solidale: Massimo Quaini tra terra e acqua - Vallerani, Francesco (Territori, 2021)
In accordance with the main goals of this collection of essays in honour of Massimo Quaini, the text focuses on a peculiar character of the Ligurian geographer's sensibility, his attention to landscape protectionresearch activity developed in the context of the humanistic geography. Starting from a personal narrative based on his own reminiscences and neglected memories, the author tries to shed light on the relationships between civil commitment and cultural reflection which characterize environmental sensitivity, bringing together his interests with Quaini's emotional geographies. Finally, some of Quaini's everyday practicalities are highlighted as the easiest doorway to improve the cognitive procedures of cultural geography.